2018
DOI: 10.14814/phy2.13833
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calpain delays early muscle atrophy after rotator cuff tendon release in sheep

Abstract: Chronic rotator cuff (RC) tears are characterized by retraction, fat accumulation, and atrophy of the affected muscle. These features pose an intractable problem for surgical repair and subsequent recovery, and their prevention may be easier than reversal. Using an established ovine model, we tested the hypothesis that inhibition of the protease calpain mitigates m. infraspinatus atrophy by preservation of the myofibers’ structural anchors in the sarcolemma (the costameres). Already 2 weeks of distal tendon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…5e7 Here we explored the course of alterations in the cellular composition of rotator cuff muscle in sheep during the first 16 weeks after tendon release, and assessed molecular composition at selected time points, in order to identify metabolic processes that are associated with the degradation of muscle fibers and lipid accumulation. 13,15,38 Our multilevel characterization exposed that atrophy and lipid accumulation in sheep infraspinatus muscle after tendon release took place in two different phases. Atrophy was essentially confined to the first 6 weeks after tendon release and was related to a slow-to-fast fiber shift of muscle composition that became manifest as early as 2 weeks after tendon release.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…5e7 Here we explored the course of alterations in the cellular composition of rotator cuff muscle in sheep during the first 16 weeks after tendon release, and assessed molecular composition at selected time points, in order to identify metabolic processes that are associated with the degradation of muscle fibers and lipid accumulation. 13,15,38 Our multilevel characterization exposed that atrophy and lipid accumulation in sheep infraspinatus muscle after tendon release took place in two different phases. Atrophy was essentially confined to the first 6 weeks after tendon release and was related to a slow-to-fast fiber shift of muscle composition that became manifest as early as 2 weeks after tendon release.…”
Section: Discussionmentioning
confidence: 96%
“…Aspects of the anatomic data (ie, the muscle volume and histologic examination) that serve as the biological background for this study have been reported previously in other form for the T2e6 and T16 groups. 13,38 Computed tomography and/or magnetic resonance imaging were performed immediately after tendon release and at the end of the experiment, in the upper body of anesthetized sheep, to estimate the volume and compositional alterations in the released infraspinatus muscle and its contralateral control. Additionally, in group T16, magnetic resonance imaging was performed at 6 weeks after tendon release.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations